A Vision of Innovation and Entrepreneurship as an engine of Economic Growth in Colombia - Molina-Muñoz, Edwin D.J. (EFIM Ediciones, 2022)
Taking into consideration the challenges posed by the current competitive environment, it is necessary to analyse in a reflexive way how this is presented in society, thus analysing the process of development of innovation as entrepreneurship in Colombia, and part of the review of articles and studies related to the concept of innovation and its relationship with entrepreneurship. country. For the achievement of this work, a methodology with a qualitative approach with a descriptive scope was used, thus managing to analyse the different most relevant and pertinent perspectives to develop the contextualization, importance and limitations of the innovation process in Colombia. The main result is a summary of the impulse of the capacity for innovation and its representation in the economic and formative aspects of the country, articulated with the analysis of the role of the state in this process. Finally, some limitations and problems associated with innovation in Latin America and Colombia are presented.